An Analysis Of The Translation Of Idiomaticexpressions In “Doraemon Gadget Cat From The Future” Volume 2 By Dhini Afiatanti And Volume 4 By Yenny Hendrawati - Rezky Ariani (Universitas Muhammadiyah Sumatera Utara, 2022)
This study deals with the “An Analysis of The Translation of Idiomatic Expresion In “Doraemon Gadget Cat From The Future Volume 2 ” By Dhini Afiatanti and volume 4 by “YennyHendrawati”. This research used qualitative research. “Doraemon comics” were taken as the source of data. The data were analyze to find out The Type of Idioms and idioms translations strategy. The type of idiom can be grouped into five categories, they are of colloquialisms, proverbs, slangs, allusions and phrasal verbs and the idiom translation strategies based on Baker can be grouped into 4, they are using an idiom of similar meaning and form, using an idiom of similar meaning but dissimilar form, translation by paraphrase, and translation by omission. The result of this research found that 49 colloquialisms, 1 proverbs, 7 slangs, 8allusions and 35 phrasal verb. Then, The Dominant type of idioms in this researcher is colloquialisms with 39 out of 100 the total idioms. For The number of idioms translations strategies are 38 the idiom translation strategies are using an idiom of similar meaning and form, 19 using an idiom of similar meaning but dissimilar form, 39 translation by paraphrase, and4 translation by omission out of the 100 idioms translated in the Comic Doraemon.